Chaperones and Beyond as Key Players in Pluripotency Maintenance - Fernandes, Camila Felix de Lima; Iglesia, Rebeca Piatniczka; Melo-Escobar, Maria Isabel; Prado, Mariana Brandão; Lopes, Marilene Hohmuth (Frontiers in Cell and Developmental Biology, 2019)
Pluripotency is orchestrated by distinct players and chaperones and their partners have emerged as pivotal molecules in proteostasis control to maintain stemness. The proteostasis network consists of diverse interconnected pathways that function dynamically according to the needs of the cell to quality control and maintain protein homeostasis. The proteostasis machinery of pluripotent stem cells (PSCs) is finely adjusted in response to distinct stimuli during cell fate commitment to determine successful organism development. Growing evidence have shown different classes of chaperones regulating crucial cellular processes in PSCs. Histone chaperones promote proper nucleosome assembly and modulate epigenetic regulation of factors involved in PSCs rapid turnover from pluripotency to differentiation. Life cycle of pluripotency proteins from synthesis and folding, transport and degradation is finely regulated by chaperones and co-factors either to maintain the stemness status or to induce cell fate commitment in PSCs. Here, we summarize current knowledge of the chaperome network that govern stemness and present the versatile role of chaperones in stem cells resilience. Elucidation of the intricate regulation of pluripotency, dissecting in detail molecular determinants and drivers, is fundamental to understand defining properties of stem cells and provide a reliable foundation for biomedical research and regenerative medicine.